Inhaled Corticosteroids for Chronic Obstructive Pulmonary Disease—The Shifting Treatment Paradigm. (3rd September 2015) - Wilkie, Morven; Finch, Simon; Schembri, Stuart
Abstract: Chronic obstructive pulmonary disease (COPD) guidelines suggest using inhaled corticosteroids (ICS) in patients with severe airflow limitation or those at high risk of exacerbations. This recommendation is based on evidence demonstrating that ICS, especially when prescribed in fixed-dose combinations (FDC) with long-acting β2 agonists (LABA), improve quality of life (QoL), decrease exacerbations and hospitalisations, and have been associated with a trend towards a reduction in all-cause mortality. Audit shows that routine prescribing practice frequently uses inhaler therapies outside current guidelines recommendations; severe to very severe disease constitutes about 20% of all COPD patients, but up to 75% of COPD patients are prescribed an ICS, with significant numbers given ICS/LABA as first-line maintenance therapy. The role of ICS in the treatment paradigm for COPD is changing, driven by the growing evidence of increased risk of pneumonia, and the introduction of a new class of FDC; LABA and long-acting muscarinic antagonists (LAMA), which simplify dual bronchodilation and present a plausible alternative therapy. As the evidence base for dual therapy bronchodilation expands, it is likely that maximal bronchodilation will move up the treatment algorithm and ICS reserved for those with more severe disease who are not controlled on dual therapy. This change has already manifested in local COPD algorithms, such as those at Tayside, and represents a significant change in recommended prescribing practice. This review reassesses the role of ICS in the shifting treatment paradigm, in the context of alternative treatment options that provide maximal bronchodilation.